Manufacturing porcine islets: culture at 22 °C has no advantage above culture at 37 °C: a gene expression evaluation. (14th August 2013) - Mueller, Kate R.; Martins, Kyra V.; Murtaugh, Michael P.; Schuurman, Henk‐Jan; Papas, Klearchos K.
Abstract Background The manufacturing process of islets includes a culture step which was originally introduced to ease the logistics of procedures in preparing the graft and transplant recipient. It has been suggested that culture at room temperature has an advantage over culture at 37 °C, in part by reducing immunogenicity via preferential elimination of contaminating cells (such as passenger leukocytes) within islets. We investigated this using islets isolated from pancreata of adult pigs. Methods Porcine islets were isolated from three donors and cultured at 37 °C for 1 day, and then under three different conditions: 37 °C for 6 days (condition A); 22 °C for 6 days (condition B); or 22 °C for 5 days followed by 37 °C for 1 day (condition C). Recovery was assessed by DNA measurement, viability by oxygen consumption rate normalized for DNA (OCR/DNA), and gene expression by RT–PCR for a series of 9 lymphocyte markers, 11 lymphokines and chemokines, and 14 apoptotic and stress markers. Results Post‐culture islet recoveries were similar for the three culture conditions. Average OCR/DNA values were 129–159 nmol/min·mgDNA before culture, and 259–291, 204–212, and 207–228 nmol/min·mgDNA, respectively, for culture under conditions A, B, and C, respectively. Irrespective of culture condition, examined gene expression in all three series of lymphocyte markers, lymphokines and chemokines, and apoptotic and stress markers manifested a statistically significant decrease upon culture for 7 days. This decrease was most dramatic for condition A: in particular, most of lymphocyte markers showed a >10‐fold reduction and also six markers in the lymphokine and chemokine series; these reductions are consistent with the elimination of immune cells present within islets during culture. The reduction was less for apoptotic and stress markers. For culture under condition B, the reduction in gene expression was less, and culture under condition C resulted in gene expression levels similar to those under condition A: this indicates that 24 h at 37 °C is sufficient to re‐equilibrate gene expression levels from those in islets cultured at 22 °C to those in islets cultured at 37 °C. Results were consistent among the preparations from the three donors. Conclusions Culture of porcine islets at 37 °C provides benefits over culture at 22 °C with respect to OCR/DNA outcomes and reduced expression of genes encoding lymphocyte markers, lymphokines and chemokines, and markers for apoptosis and stress.